Amphipoda species (Suborders: Amphilochidea and Senticaudata) from Vasiliko Bay, Cyprus: New records, information on their biogeography and an annotated checklist from the coasts of Cyprus - Rousou, Maria; Plaiti, Wanda; Lowry, Jim; Charalambous, Stephanos; Chintiroglou, Chariton Charles (Zootaxa, 2020)
Current information on soft-bottom benthic amphipod species of the south coasts of Cyprus is scarce. In the summer of 2013, a research survey was carried out, targeting the Vasiliko Bay and the nearby coastal area which is influenced by multiple human-induced stressors. Analysis of 126 samples revealed the presence of 2,122 individual amphipods (Amphilochidea and Senticaudata) belonging to 25 families and 52 species. Twenty-four species are new records for Cyprus increasing the number of amphipods to 141 species. In Vasiliko Bay, two amphipod species presented the highest abundances and were found to be constant (Microdeutopus periergos, Perioculodes longimanus), while seven are common species (Ampelisca brevicornis, Ampelisca typica, Apherusa chiereghinii, Dexamine spinosa, Harpinia crenulata, Leptocheirus pectinatus, Leucothoe incisa) and the remaining 43 species are rare. The highest amphipod total abundances and number of species were recorded in stations with dense Posidonia oceanica meadows and aquaculture units in the vicinity. Brief distributional and ecological characteristics of the identified amphipod species are given and an annotated checklist for the coasts of Cyprus is provided.